A Longitudinal Study of the Effects of Service-Learning on Physical Education Teacher Education Students - Maravé-Vivas, María; Gil-Gómez, Jesús; Valverde-Esteve, Teresa; Salvador-Garcia, Celina; Chiva-Bartoll, Oscar (Frontiers in Psychology, 2022)
Research examining Service-Learning (SL) in Physical Education Teacher Education (PETE) is ample. However, long-term investigations are still scarce and literature demands the application of this type of design to uncover the effects of SL on the long run. This study followed a longitudinal quantitative approach; thus, the participants completed the Civic Attitudes and Skills Questionnaire (CASQ) in three occasions (pretest-postest1-postest2). Results show that there exist significant differences between mean values of the global outcomes of the CASQ, concretely there was an improvement in the first interval followed by a decrease in the second period. Regarding the different dimensions of the CASQ, leadership skills, attitudes towards social justice and attitudes towards diversity showed significant differences too. This research leads towards better understanding of methodological strategies promoting quality education, positing SL as an adequate possibility in this respect, also in the long term.